2022
DOI: 10.1017/xps.2021.32
|View full text |Cite
|
Sign up to set email alerts
|

Did Ohio’s Vaccine Lottery Increase Vaccination Rates? A Pre-Registered, Synthetic Control Study

Abstract: Overcoming vaccine hesitancy is critical to containing the COVID-19 pandemic in the United States. To increase vaccination rates, the State of Ohio launched a million dollar lottery in May 2021. Following a pre-registered analysis, we estimate the effects of Ohio’s lottery program Vax-a-Million on COVID-19 vaccination rates by comparing it to a “synthetic control” composed of eight other states. We find a statistically insignificant 1.3% decrease in the full vaccination rate in Ohio at the end of the lottery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Individual states have adopted multiple incentive approaches to incentivize and stimulate COVID-19 vaccination uptake in the general population, including bonus policies (e.g., guaranteed rewards and cash) and lottery policies (e.g., scholarships and cash). Some previous studies found that COVID-19 vaccine incentive programs were associated with an increase in COVID-19 vaccination rates in some states but not in others [ 7 , 8 ], while others reported that lottery policies effectively increased COVID-19 vaccination rates in many states [ 7 , 9 , 10 ]. For example, Ohio’s lottery policy—“Vax-a-Million”—led to around 50,000 to 100,000 additional first-dose COVID-19 vaccinations [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individual states have adopted multiple incentive approaches to incentivize and stimulate COVID-19 vaccination uptake in the general population, including bonus policies (e.g., guaranteed rewards and cash) and lottery policies (e.g., scholarships and cash). Some previous studies found that COVID-19 vaccine incentive programs were associated with an increase in COVID-19 vaccination rates in some states but not in others [ 7 , 8 ], while others reported that lottery policies effectively increased COVID-19 vaccination rates in many states [ 7 , 9 , 10 ]. For example, Ohio’s lottery policy—“Vax-a-Million”—led to around 50,000 to 100,000 additional first-dose COVID-19 vaccinations [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of five studies that examined first doses [4] [7] [8] [9] [11] , three found evidence of an effect of incentives. [8] [9] [11] Of two studies that examined second doses [4] [5] , only one found an effect. [5] Two studies [6] [10] used the total rate of vaccinations combining first and second doses and one of these found an effect [10] .…”
Section: Discussionmentioning
confidence: 99%
“…[8] [9] [11] Of two studies that examined second doses [4] [5] , only one found an effect. [5] Two studies [6] [10] used the total rate of vaccinations combining first and second doses and one of these found an effect [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations